Answer:
Given : EFGH is a Parallelogram
Prove : EG Bisects HF , HF Bisects EG
Step-by-step explanation:
Proof
Check image below
2(n-9) = 3(n + 5)
2n - 18 = 3n + 15
2n - 3n = 15 + 18
-n = 33
n = -33
Answer:
Step-by-step explanation:
(1x/4 + 1/7) + (3x/8 - 1/3) = x/4 + 3x/8 + 1/7 - 1/3
= x*2/4*2 + 3x/8 + 1*3/7*3 - 1*7/3*7
= 2x/8 + 3x/8 + 3/21 - 7/21
= (2x+3x)/8 + (3-7) /21
= 5x/8 + (-4)/21
= 5x/8 - 4/21
Answer:
3x^3-18x^2+26x-8
Step-by-step explanation:
(x-4)(3x^2-6x+2)
3x^3-6x^2+2x-12x^2+24x-8
3x^3-18x^2+26x-8